Overdenture mandibular retida por implante unitário: desfechos clínicos, radriográficos e reportados pelo paciente após 5 anos de acompanhamento - Coutinho, Paula Cristina (2020)
Objective: To assess clinical, radiographic, and patient-reported outcomes of edentulous individuals rehabilitated with single-implant mandibular overdenture (SIMO) a 5-year follow-up period. Methods: A prospective clinical study was performed including edentulous individuals who received new conventional complete dentures and then an external hexagon implant (Neodent, Brazil) was placed in the mandibular midline region followed by the incorporation of a retention system (ball attachment/O'Ring, Neodent, Brazil). Data collection occurred at baseline and after 3, 6, 12, 24 and 60 months after implant loading. Outcomes included were implant stability, peri-implant soft tissue condition, periimplant marginal bone level, satisfaction with the dentures, and oral health- related quality of life impacts (OHRQoL). Also, clinical maintenance events related to the dentures were recorded. Descriptive statistics and Wilcoxon Signed Ranks Test were used for data analysis. Results: 30 out of 34 eligible participants attended the 5-year follow-up, mea age 68.1 years (SD = 7.8), 70% women. The overall implant survival rate was 95.3%. After 5 years, the OHRQoL showed a statistically significant difference between all evaluation periods compared to the baseline. There were no statistically significant differences regarding satisfaction with the maxillary prosthesis (p = 0.068) compared to the baseline period. Regarding satisfaction with the mandibular denture, there was a statistically significant difference between all evaluation periods, except for the 60-month evaluation (p = 0.213). There was an increase implant stability after 60 months and a decrease in periimplant bone level, but within expectations. The most frequent maintenance event was the O'ring matrix replacement (n = 80), followed by the repair of the denture base (n = 21). The most frequent intervention was replacement of the O'ring matrix (n = 80), followed by repair at the base of the prosthesis (n = 21). Besides, the peri-implant soft tissue condition remained stable. Conclusion: SIMO is effective in the long-term period considering the maintenance of the positive effect of the intervention in the patient-reported outcomes, the high implant survival rate, stable peri-implant condition and the occurrence of a usual number and type of maintenance events.